Sinergi Pemberdayaan Masyarakat Dengan Membangun Desa Mandiri dengan UMKM Protipe Produk Unggulan Lokal Desa Belantaraya Kecamatan Gaung Kabupaten Indragiri Hilir - Ghifariansyah, Abdu Rozaq; Sulistyani, Andri; Putri, Nurdiana; Stiawan, Ahmad Adi; Ananta Pristianta, Ananta Pristianta; Yaqin, Siti Ainul; Sari, Yesi Puspita; Anugrah, Muhammad Irvan; Riyandi, Fahnur (Unri Conference Series: Community Engagement, 2024)
UMKM Prototype is a concept where Micro, Small and Medium Enterprises (UMKM) create new products or services that are still in the experimental or early development stages. This is like creating a prototype or initial model of a physical product, but in a business context. The prototype UMKM show that the synergy between the village government, community and the private sector in encouraging the development of prototype UMKM has succeeded in improving the community's economy. The superior local products produced are not only able to meet the needs of the local market, but also have the potential to penetrate a wider market. Prototype UMKM Empowerment aims to analyze the synergy of community empowerment in building independent villages in Belantaraya Village, Gaung District, Indragiri Hilir Regency through the development of prototype UMKM based on local superior products. Innovation in the production and marketing processes of products, as well as support for organic product certification have prototype for local superior products in the Wilderness village. By creating prototype UMKM into superior products, Belantarya villages can create employment opportunities for the people of Wilderness villages, increase people's income and reduce the unemployment rate in Wilderness villages.